Effect of cobalt ions doping on morphology and electrochemical properties of hydroxyapatite coatings for biomedical applications - Meysam Safari-Gezaz; Mojtaba Parhizkar; Elnaz Asghari (Scientific Reports)
Abstract Hydroxyapatite (HA) is an engineered biomaterial that closely resembles the hard tissue composition of humans. Biological HA is commonly non-stoichiometric and features lower crystallinity and higher solubility than stoichiometric HA. The chemical compositions of these biomaterials include calcium (Ca), phosphorus (P), and trace amounts of various ions such as magnesium (Mg2+), zinc (Zn2+), and strontium (Sr2+). Significantly, these ions are essential for the metabolic processes of hard tissues. This study involved the application of Co2+-doped HA coatings at different concentrations (5%, 10%, and 20% by weight) onto Ti-6Al-4V, utilizing the spin-coating method. The FTIR, XRD, FESEM, EDS, and AFM techniques were utilized to analyze the coated substrates. Tetraethyl orthosilicate (TEOS (T)) was employed as a binding agent to enhance adhesion and reduce surface cracks in the coating. The adhesion strength of coatings applied to Ti-6Al-4V was assessed for use in biomedical applications. Polarization and electrochemical impedance spectroscopy (EIS) studies in a simulated body fluid (SBF) solution were conducted to evaluate the corrosion behavior of the coatings. The corrosion behavior of the coated samples increased significantly compared to the substrate. The 10Co/HA/T coating demonstrated the highest charge transfer resistance (Rct) value of 13.40 MΩ × cm2, whereas the uncoated substrate exhibited the lowest Rct of 0.14 MΩ × cm2. A cell viability assay was conducted utilizing MG-63 cells for the Ti-6Al-4V and coatings, which prepared coatings demonstrated outstanding biocompatibility. Based on this study, the 10Co/HA/T coating was identified as the most promising sample. These findings suggest that surface modification of Ti-6Al-4V through Co2+-doped HA coatings offers a viable strategy for enhancing its performance in biomedical applications.